FORMAÇÃO INTEGRADA NA CONSTRUÇÃO CIVIL PROGRAMA FICC: RELATO DE EXPERIÊNCIA - Fontenelle, Maria Aridenise Macena; Macena, Raimunda Hermelinda Maia; Rodrigues, Bruno Noronha (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The objective of this work is to describe educational practices on the enviroment and working conditions in the civil construction industry carried out in fifteen classes of construction workers within the framework of the Integrated Civil Construction Training (FICC) project. The FICC university extension program integrates FICC SABENDO, FICC SAUDÁVEL and FICC VERDE projects, respectively in the areas of productivity and quality; worker health and first aid; and waste management at the construction site. For that, a plan was drawn up for the realization of the workshops held with about 150 workers on the environment and working conditions in the construction industry. Considering the activities carried out at each meeting, it was observed that the collaborators participated in the activities proposed and demonstrated knowledge about the topics discussed.